Horta agroecológica: construção do conhecimento cientifíco no espaço escolar - Buzato, Gláucia Cristina Silva (Universidade Federal de São Carlos, 2023)
The present work seeks to evaluate the process of developing scientific knowledge, making its application familiar and affective through a school garden based on agroecology. This operated as a facilitating pedagogical tool for children's learning, mainly because they live in rural areas and are familiar with planting. During the research, the participants were invited to express themselves through drawings, since the imagery expression accompanies child development like a radiograph, where we can analyze how they relate to reality and cultural elements of the surroundings they live in; consequently, the drawing is the graphic “translation” of this perception. The research aimed to identify the development of scientific knowledge having as reference the reading of the drawings produced. The question that guided the research was: what are the meanings and scientific learning attributed to the growth of plants in the school garden? The participating subjects were students from a municipal school within the metropolitan region of Sorocaba-SP and enrolled in the 5th year, aged between 9 and 10 years. The methodology used was action-research and Peircean Semiotics was used as an instrument for analyzing the students' image production. The research started in May 2021, during the week of the environment and ended in December of the same year, with the end of the school year. The analyzes satisfactorily identified evidence of the development of scientific knowledge and it is possible to observe, through imagery language, a cognitive formation different from the initial one brought by the participants.
Agroecological garden: construction of scientific knowledge at school
Keywords: Ensino de Ciências; Teoria da Complexidade; Alfabetização científica; Ensino fundamental; Science Teaching; Elementary School; Scientific literacy; Complexity Theory; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::FUNDAMENTOS DA EDUCACAO